An Equilibrium Analysis of the Gender Wage Gap - Elisabeth Hermann Frederiksen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
This paper develops a theory of the gender wage gap. In a general equilibrium model, spouses devide their labor between a formal sector and a home sector. Due to indivisibility effects, productivity of labor in the formal sector is negatively related to labor used in the home; at the same time labor inputs are complementary in home production. We show that initial beliefs about the gender wage gap are self-fulfilling, and a central result is multiplicity of equilibria. Spouses allocate their labor equally, if they expect to earn the same wage rates, which ex post reinforces equal wage rates; whereas they allocate their labor differently, if they expect to earn different wage rates. The latter situation manifests itself in a gender wage gap. By use of numerical examples, we show that welfare is highest when spouses allocate labor equally. We relate this finding to policy recommendations.
Keywords: D13; J16; J22; J30; 330; gender wage gap; household models; household production; labor markets